On the molecular structure of Remdesivir for the treatment of Covid-19. Issue 9 (11th August 2021) - Sheikholeslami, S. M.; Jahanbani, A.; Shao, Z.
Abstract: (SARS-CoV-2), was first identified in December 2019 as the cause of a respiratory illness designated coronavirus disease 2019, or Covid-19. Several therapeutic agents have been evaluated for the treatment of Covid-19, but none have yet been shown to be efficacious. Remdesivir (GS-5734), an inhibitor of the viral RNA-dependent, RNA polymerase with inhibitory activity against SARS-CoV and the Middle East respiratory syndrome (MERS-CoV), was identified early as a promising therapeutic candidate for Covid-19 because of its ability to inhibit SARS-CoV-2 in vitro. Besides, in nonhuman primate studies, remdesivir initiated 12 hours after inoculation with MERS-CoV9, 10 reduced lung virus levels and lung damage. In the field of Medical Science, concerning the definition of the topological index on the molecular structure and corresponding medical, biological, chemical, pharmaceutical properties of drugs can be studied by the topological index calculation. In this paper, we compute some of the general temperature topological properties of remdesivir that the results in this paper may be useful in finding new drug and vaccine for the treatment and prevention of COVID-19.